Therapeutic group for obesity: Adopted methodology, nutritional profileand achieved impact - de Melo, Letícia Maria; Rodrigues Carvalho Cruz, Nilcemar; Souza Santos, Virgínia; Martins Moreira, Marlon (Guará Journal, 2025)
The objective of this study was to implement a weight management group among overweight individuals to promote nutritional assessment and re-education. The sample consisted of 28 adult women. For eight weeks, the group received guidance on healthy eating, exercised, and had their weight assessed. 64.2% (n=18) of the group adhered to the program, and of these, 94.4% (n=17) achieved weight loss. The proposed intervention was effective, but program adjustments are needed to improve adherence among patients.
Keywords: Nutrition education; Obesity and weight control